Assessment the Quantity and Quality of Prenatal Care referred to Maternity and Obstetrics\' Facility - Razieh Zahedi; Samira Rahmanian; Vahid Kohpeima Jahromi (Kerman University of Medical Sciences, 2016)
Assessment the Quantity and Quality of Prenatal Care referred to Maternity and Obstetrics' Facility Zahedi Razieh1, Rahmanian Samira2, Kohpeima JahromiVahid3* Received: 21. 10. 2015             Revised: 06. 02. 2016             Accepted: 15. 03. 2016 1.PhD Student, Research Center for Modeling in Health, Institute for Future Studies in Health, Kerman University of Medical Sciences, Kerman, Iran. 2. MSc, Deputy of Health, Jahrom University of Medical Sciences, Jahrom, Iran. 3. PhD Student, Health Services Management Research Center, Institute for Futures Studies in Health, Kerman University of Medical Sciences, Kerman, Iran. *Correspondence: Haft bagh alavi Highway, Kerman University of Medical Sciences,School of Management and Medical Informatics. Tel: 071-54340406                 Fax: 071-54344002                Email: vahidkouh@yahoo.com Abstract  Introduction: Prenatal cares are provided with the aim of maintaining a healthy pregnancy in regard to the physical and psychological health of both mother and her baby. This study was carried out to assess the quantity and quality of prenatal care in Jahrom/ Iran. Method: The cross-sectional study was conducted on 531 urban and rural pregnant women. Data were collected by "Integrated Management Evaluation System" check list that was prepared by Health Ministry. The quantity of care was classified as adequate in case of at least 6 prenatal visits before the end of the first trimester and the first visit before the end of the first trimester; otherwise, it was classified as inadequate. The quality of care was determined as appropriate and inappropriate based on the standards of prenatal care. Results: In whole, 242 pregnant women had received adequate care and the rate of adequate care in rural areas was significantly higher than that in urban area. The quantity of care in urban area (45%) was significantly higher than in rural area (51%). The quality of care was appropriate in 333 women and it was significantly higher in rural area (68.9%) than in urban area (56.6%). Urinary infection and anemia were significantly more prevalent in rural women than in urban women. Conclusion: The rate of pregnancy complications was higher in rural women despite better quality and quantity of prenatal cares in rural area. Therefore, it is necessary that health workers pay more attention to the pregnant women's education and control of complications. Keywords: Pregnant women, Quantity of prenatal care, Quality of prenatal Care, "Integrated Management Evaluation System" check list, Standard healthcare Citation: Zahedi R, Rahmanian S, Kohpeima Jahromi V.Assessment the Quantity and Quality of Prenatal Care referred to Maternity and Obstetrics' Facility. Journal of Health Based Research 2015; 1(3): 199-213.